"The (Un)Sustainability of the Sale of Goods in Directive (EU) 2019/771" - Oliveira da Silva, Maria Miguel (2024)
Publisher Copyright: © 2024 selection and editorial matter, Marta Santos Silva, Andrea Nicolussi, Christiane Wendehorst, Pablo Salvador Coderch, Marc Clément and Fryderyk Zoll; individual chapters, the contributors.